Occupational stress, self-undermining behavior, and perceived social support among Indonesian seafarers: A quantitative correlational study - Nuramaliah, Nuramaliah; Kastanya, Lidia (Empathy : Jurnal Fakultas Psikologi, 2025)
This study aimed to examine the correlational relationship between work stress and self-undermining behavior on perceived social support among Indonesian seafarers. The sample consisted of 185 seafarers working on domestic and international shipping routes. Data were collected using standardized questionnaires, including the Work Stress Scale, Self-Undermining Behavior Scale, and the Multidimensional Scale of Perceived Social Support (MSPSS). Analyses were conducted using the Kolmogorov-Smirnov test for normality, Spearman correlation, and multiple linear regression. Results indicated that work stress (r = -0.177, p = 0.016) and self-undermining behavior (r = -0.176, p = 0.017) were significantly negatively correlated with social support, suggesting that higher work stress or self-undermining behavior is associated with lower perceived social support. However, multiple regression analysis revealed that these variables simultaneously did not significantly predict social support (R² = 0.004, p = 0.703), indicating that other factors contribute more substantially to seafarers’ perceptions of social support. These findings highlight the need for organizational interventions to strengthen social support systems in seafarers’ work environments and offer theoretical implications for understanding the dynamics of work stress and self-undermining behavior in maritime work contexts.